The efficacy of adjuvant mitotane therapy and radiotherapy following adrenalectomy in patients with adrenocortical carcinoma: A systematic review and meta-analysis - Tsuboi, Ichiro; Kardoust Parizi, Mehdi; Matsukawa, Akihiro; Mancon, Stefano; Miszczyk, Marcin; Schulz, Robert J; Fazekas, Tamás; Cadenar, Anna; Laukhtina, Ekaterina; Kawada, Tatsushi; Katayama, Satoshi; Iwata, Takehiro; et al. (Urologic oncology, 2025)
Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy with a high recurrence rate after surgical therapy with curative intent. Adjuvant radiotherapy (RT) and mitotane therapy have been proposed as options following the adrenalectomy. However, the efficacy of adjuvant RT or mitotane therapy remains controversial. We aimed to evaluate the efficacy of adjuvant therapy in patients who underwent adrenalectomy for localised ACC. The PubMed, Scopus, and Web of Science databases were queried on March 2024 for studies evaluating adjuvant therapies in patients treated with surgery for localized ACC (PROSPERO: CRD42024512849). The endpoints of interest were overall survival (OS) and recurrence-free survival (RFS). Hazard ratios (HR) with 95% confidence intervals (95%CI) were pooled in a random-effects model meta-analysis. One randomized controlled trial (n = 91) and eleven retrospective studies (n = 4,515) were included. Adjuvant mitotane therapy was associated with improved RFS (HR: 0.63, 95%CI: 0.44-0.92, p = 0.016), while adjuvant RT did not reach conventional levels of statistical significance (HR:0.79, 95%CI:0.58-1.06, p = 0.11). Conversely, Adjuvant RT was associated with improved OS (HR:0.69, 95%CI:0.58-0.83, p<0.001), whereas adjuvant mitotane did not (HR: 0.76, 95%CI: 0.57-1.02, p = 0.07). In the subgroup analyses, adjuvant mitotane was associated with better OS (HR:0.46, 95%CI: 0.30-0.69, p < 0.001) and RFS (HR:0.56, 95%CI: 0.32-0.98, p = 0.04) in patients with negative surgical margin. Both adjuvant RT and mitotane were found to be associated with improved oncologic outcomes in patients treated with adrenalectomy for localised ACC. While adjuvant RT significantly improved OS in general population, mitotane appears as an especially promising treatment option in patients with negative surgical margin. These data can support the shared decision-making process, better understanding of the risks, benefits, and effectiveness of these therapies is still needed to guide tailored management of each individual patient.
Keywords: adjuvantní radioterapie; výsledek terapie; Chemotherapy, Adjuvant; Adrenocortical carcinoma; adrenalektomie; adrenokortikální karcinom; Radiotherapy, Adjuvant; Adrenal Cortex Neoplasms; mitotan; Mitotane; Adjuvant therapy; Adrenocortical Carcinoma; Treatment Outcome; hormonální protinádorové látky; lidé; Humans; adrenokortikální nádory; Radiotherapy; adjuvantní chemoterapie; Adrenalectomy; Antineoplastic Agents, Hormonal